CmWRKY15-1 Promotes Resistance to Chrysanthemum White Rust by Regulating CmNPR1 Expression - Gao, Ge; Jin, Ruibing; Liu, Di; Zhang, Xin; Sun, Xiaomei; Zhu, Pengfang; Mao, Hongyu (Frontiers in Plant Science, 2022)
Chrysanthemum white rust, a disease caused by the fungus Puccinia horiana Henn., seriously impairs the production and ornamental value of chrysanthemums. We previously isolated the disease-resistance gene CmWRKY15-1 from chrysanthemum and generated CmWRKY15-1 transgenic plants. Here, we determined that CmWRKY15-1-overexpressing lines of the susceptible cultivar 'Jinba' show higher defensive enzyme activity and lower H2O2 levels than wild type after inoculation with P. horiana, indicating that CmWRKY15-1 positively regulates plant responses to P. horiana. To further explore the mechanism underlying this effect, we performed RNA sequencing using the leaves of wild-type and CmWRKY15-1-RNA interference lines of the resistant cultivar 'C029' after treatment with P. horiana. We identified seven differentially expressed genes in the salicylic acid pathway, including CmNPR1 (Nonexpressor of pathogenesis-related genes 1), encoding an important regulator of this pathway. We isolated the CmNPR1 promoter by hiTAIL-PCR and predicted that it contains pathogen-induced W-box elements. The promoter region of CmNPR1 was activated by P. horiana in a GUS activity assay. Yeast one-hybrid assays showed that CmWRKY15-1 binds to the CmNPR1 promoter region to regulate its expression. Finally, we confirmed the interaction between CmWRKY15-1 and CmNPR1 in a bimolecular fluorescence complementation assay. We propose that CmWRKY15-1 interacts with CmNPR1 to activate the expression of downstream pathogenesis-related genes that enhance resistance to P. horiana through the salicylic acid pathway. These findings shed light on the mechanism underlying resistance to chrysanthemum white rust.